Kingdom, church and civil society: A theological paradigm for civil action - Vorster, J.M. (HTS teologiese studies, 2015)
This article deals with the role that churches can and should play in civil society to develop societal morally. The central-theoretical argument is that the biblical notion of the kingdom of God can, when it is systematically and theologically developed, offer an acceptable foundation for the civil action of churches. In light of this the article takes a new look at the neo-Calvinist view on church and society. The kingdom implies the life encompassing governance of God, the formation of the church and the creation of a moral sense amongst people. The church can, from the perspective of the kingdom, be seen as a community within which Christians should be equipped for social action. The church is a power station which carries forth the light of the Gospel by means of the social involvement of believers in civil society. Christians can, based on natural law, work with civil organisations to pursue the common good of the community. Such collaboration becomes possible only when civil society works purpose- and not paradigm-driven. Based on the moral sense that is founded in natural law, Christians can be socially active within civil society in search of the greatest benefit for all people within the community.